Human rights in Islamic North Africa : clashes between constitutional laws and penal codes - Udogu, E. Ike (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2020)
'It is one thing to craft superb human rights tenets in a constitution and another to enforce such policies off paper. This book explores the contradictions between interpretations of constitutional tenets and the dogmas contained in the penal code of Islamic North Africa-particularly in regard to Algeria, Egypt, Libya, Morocco, and Tunisia. Provided are brief histories of each country that connect the colonial past to present-day human rights records. The author also suggests ways in which to mitigate human rights infractions to advance peaceful coexistence that could promote political and economic development.'--
Algeria -- Egypt -- Libya -- Morocco -- Tunisia.
Bibliography : page 229-244.
Buku bacaan asas siswazah Fakulti Pengajian Islam.
Keywords: Criminal law -- Africa, North; Law -- Africa, North -- Islamic influences; Criminal law -- Egypt; Law -- Egype -- Islamic influences